THE EUROPEAN UNION'S EURO 1 TO EURO 6 PROGRAMME - Kautsar, Fawwas Ranu (Journal of Social Political Sciences, 2024)
This study examines the labor market opportunities for traditional medical practitioners in light of Government Regulation Number 103 of 2014, focusing on the role of traditional health practices during the COVID-19 pandemic. The research investigates how natural remedies, particularly herbal medicines, continue to be sought by individuals to manage common health issues like fever, flu, and cough—symptoms similar to those of COVID-19, though not necessarily indicative of the virus. Despite the rise of modern healthcare, the findings reveal that traditional medicine remains highly valued within communities, with substantial demand for services offered by traditional healers. The study suggests that even with the implementation of regulations to formalize and standardize healthcare practices, the labor market for traditional medical practitioners remains robust. This demonstrates the resilience and ongoing relevance of traditional health services, highlighting their crucial role within the broader healthcare landscape.